BS EN 61076-8-108. Connectors for electrical and electronic equipment. Product requirements. Part 8-108. Power connectors. Detail specification for 2P 250 A, 1 000 V plus 2P 5 A 50 V rectangular housing shielded connectors with IP65/IP68 degree of protection when mated and locked, and IPXXB when unmated (22nd July 2021) - British Standards Institution,
No abstract available